Heating and evaporation of a new gasoline surrogate fuel: A discrete multicomponent modeling study. (1st December 2015) - Su, Mengying; Chen, C.P.
Highlights: Gasoline is modeled by a six-component surrogate fuel covering three major hydrocarbon groups. The new surrogate emulates real gasoline distillation curve and contains the toluene reference fuel components. Discrete multicomponent model is used to investigate heating and evaporation of gasoline fuel droplets. Abstract: In Gasoline Direct Injection (GDI) engines, a fuel spray is injected directly into the cylinder during the compression stroke, creating a fuel–air mixture with an ignitable composition at the spark gap at the time of ignition. Spraying droplet breakup, heating and evaporation is essential for the mixture preparation and the ignition/combustion. For numerical modeling of spray evaporation and combustion, it is impractical to include all real components. In this study, a new 6-component surrogate mixture composed of i-pentane/n-heptane/toluene/iso-octane/n-propyl cyclohexane/iso-undecane is developed to match the targeted gasoline in terms of thermo-physical properties and experimental distillation curve. This new surrogate also covers TRF (toluene reference fuel) components, which are the three basic components for ignition modeling. This allows both physical and chemical modeling of gasoline using only one surrogate. This new surrogate fuel is implemented into an existing modeling methodology which simultaneously accounts for finite conductivity, finite mass diffusivity and turbulence effects within atomizing multicomponent liquid fuel sprays. The main purpose of this study is to perform analysis of heating and evaporation of the new surrogate gasoline. Both normal evaporation and flash boiling evaporating processes are investigated.